2019
DOI: 10.37362/jch.v3i3.225
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Study On Drug Users Class IIa Bulukumba Drugs

Abstract: Illegal drugs are solid or liquid substances, gases that cause physical and psychological changes in the body, almost all drugs affect the central nervous system, drugs act on the brain and can affect anesthesia, view the emergence of side effects and the high persistence to use illegal drugs without being prescribed by a doctor and can cause drug addiction or addiction. Some factors cause drug users, namely environmental factors, family factors and social factors, and 179 drug users in Bulukumba class IIA pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The internal factors in question are age, marital status, education level, and length of legal period and for external factors, behavioral habituation from different environments was previously included in the existing programs in prisons. The current study conducted by (Misrawati, Asri, & Tenriwati, 2019) found that the most frequent occurrence of depression in prisons is drug cases.…”
Section: Discussionmentioning
confidence: 55%
“…The internal factors in question are age, marital status, education level, and length of legal period and for external factors, behavioral habituation from different environments was previously included in the existing programs in prisons. The current study conducted by (Misrawati, Asri, & Tenriwati, 2019) found that the most frequent occurrence of depression in prisons is drug cases.…”
Section: Discussionmentioning
confidence: 55%